2020
DOI: 10.21203/rs.3.rs-74076/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High levels of low back disability, but not low back pain intensity, are associated with reduced physical activity: a community-based, cross-sectional study

Abstract: Background Although clinical guidelines recommend physical activity for low back pain (LBP), our understanding of the physical activity undertaken by people with LBP is limited. We examined the amounts, intensities and types of physical activity performed by community-based women with different levels of pain and disability. Methods 542 women were invited to participate. Physical activity was measured using the International Physical Activity Questionnaire, and LBP and disability were assessed using the Chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Additionally, we also found that there was a statistically significant positive correlation between moderately vigorous activities (i.e., carrying light loads, bicycling at a regular pace, doubles tennis, heavy lifting, digging, aerobics, or fast bicycling) and (8) revealed that a regular exercise routine is a key strategy for physical health during the COVID-19 pandemic. Contrariwise, another study by Alyousef et al (9) showed that the severity of low back pain and physical activity level were not related, but they disclosed that high levels of low back disability were associated with reduced physical activity, including less total, moderate, vigorous, and discretionary types of activity. Amorim et al (10) reported that occupational physical activity, such as carrying a heavy weight while inclined and awkward postures (e.g., bending, twisting, squatting, and kneeling) are associated with a higher prevalence of recurrent low back pain.…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, we also found that there was a statistically significant positive correlation between moderately vigorous activities (i.e., carrying light loads, bicycling at a regular pace, doubles tennis, heavy lifting, digging, aerobics, or fast bicycling) and (8) revealed that a regular exercise routine is a key strategy for physical health during the COVID-19 pandemic. Contrariwise, another study by Alyousef et al (9) showed that the severity of low back pain and physical activity level were not related, but they disclosed that high levels of low back disability were associated with reduced physical activity, including less total, moderate, vigorous, and discretionary types of activity. Amorim et al (10) reported that occupational physical activity, such as carrying a heavy weight while inclined and awkward postures (e.g., bending, twisting, squatting, and kneeling) are associated with a higher prevalence of recurrent low back pain.…”
Section: Discussionmentioning
confidence: 97%